Setting the basis for a long-term monitoring network of intertidal seaweed assemblages in northwest Spain. (September 2020) - Barrientos, Sara; Barreiro, Rodolfo; Cremades, Javier; Piñeiro-Corbeira, Cristina
Abstract: A distortion of coastal communities has been reported along the European Atlantic in recent years. In NW Spain, the lack of studies focusing on long-term changes was resolved when several common perennial seaweeds were shown to have diminished in occurrence between 1998/99 and 2014. To ascertain whether their decline reflected a genuine long-term trend, the same network of monitoring locations and the same set of perennial seaweeds was re-surveyed in 2018. Contrary to our expectations, the average number of species per site increased in semi-exposed and semi-sheltered locations to become statistically indistinguishable from 1998/99 estimates. Nevertheless, site occupancy rates continued to be below 1998/99 estimates for several seaweeds, and warming, both from rising average temperatures and from more frequent and intense marine heatwaves in autumn, seems a plausible explanation for their decline. The benefits of routinely monitoring a network of fixed stations, especially when they are subject to different levels of wave exposure, are discussed. Highlights: A fixed network of biomonitoring stations allows a better assessment of global change effects. The abundance of some intertidal perennial seaweeds partially recovered from lows recorded in 2014. However, the richness of intertidal assemblage has worsened since 1998. Global warming also reshaped the distribution of some seaweeds. Temperature, marine heat waves and extreme wave events increased over the last decades.